The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000115028
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Anatomy of Craniofacial Sutures

Abstract: Sutures are fibrous joints in the vertebrate skull. They consist of two bone ends and intervening fibrous tissue which differentiates from embryonic mesenchyme. Sutures are not merely articulations between bones they are primary sites of osteogenesis mediating much of the growth of the face and skull vault. In this chapter the development of sutures will be described including the origin of sutural tissues, the determinants of suture location, and suture morphology. Also, the main functions of sutures will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 53 publications
2
109
0
4
Order By: Relevance
“…In this study, a specific choice in the biochemical reaction term led to the formation of labyrinthic patterns that resembled sutures. Nevertheless, even though morphogens are determinants of embryonic suture development [2,9], mechanical forces have to be taken into account in order to explain how sutures grow after birth and develop their peculiar architecture [2]. Another morphogenetic model for sutures has been recently proposed [16] and involved 'viscous fingering' phenomena similar to those occurring between two immiscible liquids with different viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a specific choice in the biochemical reaction term led to the formation of labyrinthic patterns that resembled sutures. Nevertheless, even though morphogens are determinants of embryonic suture development [2,9], mechanical forces have to be taken into account in order to explain how sutures grow after birth and develop their peculiar architecture [2]. Another morphogenetic model for sutures has been recently proposed [16] and involved 'viscous fingering' phenomena similar to those occurring between two immiscible liquids with different viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…[26] In the skull (and probably in the shell of the turtle), sutures are not only articulations between bones, but also areas of osteogenesis, in which osteoprogenitor cells proliferate, differentiate, and allow bone growth. [27] Thus, the suture maintains a space between opposing bone margins so that they do not unite, and continued bone growth can occur. The growth of adjoining dermal bones Figure 1.…”
mentioning
confidence: 99%
“…In the human skull, suture closure occurs in early adulthood (25-30 years of age) for calvarial sutures, while facial sutures close only in late adulthood (7 th to 8 th decade of life). [27] However, it is not known when (if ever) the sutures of the shell of turtles close. We have found that the sutures were open in all the turtles examined, including large, fully mature turtles, which reached their adult size.…”
mentioning
confidence: 99%
“…In the developing calvarium, appositional bone growth increases bone thickness. 23 Disturbed appositional bone growth in HGPS has been suggested by the observation of laminations beneath the periosteum of long bones on radiographs. 13 A predisposition toward skull fractures has been reported in HGPS.…”
Section: Calvarial and Skull Base Changesmentioning
confidence: 99%